Perfect Non-Neighbor Harmonic Graphs - Rizwana, A; Jeyakumar, G; Mohamed Ismail, M (International Journal of Computer Sciences and Engineering, 2025)
Computation of topological indices is a recent research problem in mathematical and computational chemistry. Based on the number of non-neighbors of a vertex u in a graph G, non-neighbor harmonic index is defined. In this paper we compute the non-neighbor harmonic polynomial of some graphs. We develop a MATLAB program for computing the roots of the non-neighbor harmonic polynomial and hence define the perfect non-neighbor harmonic graphs.